Higher-Order Dynamic Delay Differential Equations on Time Scales - Hua Su; Lishan Liu; Xinjun Wang (Journal of Applied Mathematics, 2012)
We study the existence of positive solutions for the nonlinear four-point singular boundary value problem with higher-order p-Laplacian dynamic delay differential equations on time scales, subject to some boundary conditions. By using the fixed-point index theory, the existence of positive solution and many positive solutions for nonlinear four-point singular boundary value problem with p-Laplacian operator are obtained.